Highlights from the Faraday Discussion 296: quantum effects in small molecular systems, 10–12 September 2018, Edinburgh, United Kingdom. Issue 97 (26th November 2018) - Ban, Loren; Besemer, Matthieu; Mouhib, Halima
Abstract : Exciting discussions on the impact of quantum effects in small molecular systems took place in the historical city of Edinburgh this fall 2018 in the unique conference format of the Faraday Discussions. Abstract : Exciting discussions on the impact of quantum effects in small molecular systems took place in the historical city of Edinburgh this fall 2018 in the unique conference format of the Faraday Discussions. During this three day conference meeting close to Holyrood Park, 65 leading experts from all over the world came together to discuss the developments, advances and challenges in the wide field of quantum effects in small molecular systems, either isolated or embedded into clusters, clathrates or cold matrices. The meeting clearly reflected the importance of the accurate description, characterization and prediction of quantum effects in isolated, solvated and complexed molecular systems, while allowing the community to crystallize future perspectives and directions in the field, as well as applications in chemistry, physics, biology, environmental sciences and industry.